(untitled) (The Review of Diabetic Studies, 2025)
Paramedics play a crucial role in the early recognition and management of geriatric emergencies, which are increasing due to the global rise in the aging population. Older adults frequently present with complex, atypical symptoms related to comorbidities, polypharmacy, and age-related physiological changes, making timely identification and intervention challenging in the prehospital setting. This review explores the epidemiology of geriatric emergencies, the impact of physiological aging on clinical presentations, and the role of paramedics in assessing and managing common emergencies such as cardiovascular, neurological, respiratory, and traumatic events. Paramedics face challenges in recognizing atypical presentations, navigating communication barriers, and operating with limited diagnostic tools. However, their unique position to access patients’ homes, perform comprehensive assessments, and initiate early treatments can significantly improve outcomes. Effective management requires adapting protocols to geriatric physiology, utilizing screening tools for frailty and cognitive impairment, and ensuring medication safety. Paramedic training increasingly incorporates geriatric-specific education, simulation-based scenarios, and cultural competence to prepare providers for the complex needs of older adults. Future directions include integrating artificial intelligence to support clinical decision-making, expanding community paramedicine programs, and developing targeted policies to standardize geriatric emergency care. Global best practices focus on comprehensive geriatric assessments, multidisciplinary collaboration, and context-appropriate protocols. Strengthening paramedics’ role in geriatric emergency care is critical to meet the evolving needs of aging populations worldwide.